Broken bar and end-ring faults: analysis of their effects on the rotor cage currents. Issue 6 (2nd November 2015) - Mesbeh, Amina; Jarboui, Marwen; Masmoudi, Ahmed
Abstract : Purpose: – The purpose of this paper is to investigate the effects of different faulty scenarios on the induction motor (IM) operation with emphasis on the currents in the rotor bar and end rings. Design/methodology/approach: – The modeling of the IM followed by a graphical representation-based analysis of the rotor steady-state currents under healthy operation is treated. Then, a case study is considered in order to investigate different faulty scenarios with a focus on the rotor cage currents. Findings: – It has been found that the rotor faults greatly affect the currents in the bars and in the end rings both in amplitude and in harmonic content. These vary according to the relative positions with respect to the fault such that: the currents in the bars adjacent to the faulty one(s) have the highest amplitudes with the lowest harmonic content; and the ones in the ring portions adjacent to the faulty one have the lowest amplitudes with the highest harmonic content. Research limitations/implications: – Although the simulated model has confirmed the well known IM behavior under healthy operation, it would be appreciated if the obtained results under faulty operation would be validated by finite element analysis. Practical implications: – It is of great interest to investigate the effects of faulty scenarios on the rotor cage currents, in order to take appropriate actions starting from the design of the IM. Originality/value: – A deep investigation (including the waveforms, the phasor diagrams and the harmonic content) of the effects of different faulty scenarios on the IM rotor cage currents represents the major contribution of this work.